Stereotactic Radiosurgery and Stereotactic Body Radiation Therapy Cost-Effectiveness Results - Bijlani, Akash; Aguzzi, Giovanni; Schaal, David; Romanelli, Pantaleo (Frontiers in Oncology, 2013)
Objective: To describe and synthesize the current stereotactic radiosurgery (SRS) and stereotactic body radiation therapy (SBRT) cost-effectiveness research to date across several common SRS and SBRT applications. Methods: This review was limited to comparative economic evaluations of SRS, SBRT and alternative treatments (e.g., other radiotherapy techniques or surgery). Based on PubMed searches using the terms, “stereotactic”, “stereotactic radiosurgery”, “stereotactic radiotherapy”, “stereotactic body radiotherapy”, “stereotactic body radiation therapy”, “stereotactic ablative radiotherapy”, “economic evaluation”, “quality adjusted life year (QALY)”, ”cost”, “cost effectiveness”, “cost utility” and “cost analysis”, published studies of cost-effectiveness and health economics were obtained. Included were articles in peer-reviewed journals that presented a comparison of costs between treatment alternatives from January 1997 to November 2012. Papers were excluded if they did not present cost calculations, therapeutic cost comparisons, or health economic endpoints. Results: Clinical outcomes and costs of SRS and SBRT were compared to other therapies for treatment of cancer in the brain, spine, lung, prostate and pancreas. Treatment outcomes for SRS and SBRT are usually superior or comparable, and cost-effective, relative to alternative techniques. Conclusion: Based on the review of current SRS and SBRT clinical and health economic literature, from a patient perspective, SRS and SBRT provide patients a clinically-effective treatment option, while from the payer and provider perspective, SRS and SBRT demonstrate cost-savings.